2022
DOI: 10.1002/ece3.8931
|View full text |Cite
|
Sign up to set email alerts
|

Pan‐European phylogeography of the European roe deer (Capreolus capreolus)

Abstract: Climate fluctuations during the Last Glacial Period between 115,000 and 11,500 years ago (Lokrantz & Sohlenius, 2006) played an important role in shaping the current species composition, distribution, and genetic diversity of mammals in Europe. During glaciations, the ranges of cold sensitive species were limited to refugial areas located in the Balkan, the Iberian and the Apennine Peninsulas (Hewitt, 2004;Taberlet et al., 1998) and south-eastern part of the continent (the Black Sea region and the Caucasus Mts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 73 publications
4
15
0
Order By: Relevance
“…The European roe deer (Capreolus capreolus) is one of the most abundant wild ungulates and an important hunting species that is distributed across the European continent from the Mediterranean to Scandinavia (Apollonio et al 2010, Plis et al 2022. Evaluation of genetic diversity, parentage testing and animal identification are essential for the protection and efficient management of animal populations.…”
Section: Introductionmentioning
confidence: 99%
“…The European roe deer (Capreolus capreolus) is one of the most abundant wild ungulates and an important hunting species that is distributed across the European continent from the Mediterranean to Scandinavia (Apollonio et al 2010, Plis et al 2022. Evaluation of genetic diversity, parentage testing and animal identification are essential for the protection and efficient management of animal populations.…”
Section: Introductionmentioning
confidence: 99%
“…The studies on karyotypes showed that all populations of the European roe deer have the same chromosome set: 2n = 70, whereas all populations of the Siberian roe deer are characterized by the presence of one or more microchromosomes belonging to a group of ancestral chromosomes known as B-chromosomes: 2n = 70 + (1--14) (Danilkin, 1995). Various studies using mitochondrial and microsatellite markers in European roe deer populations revealed a geographic pattern in the population structure, with generally high levels of genetic variation and traces of introgression between Siberian and European roe deer on large areas of Central and Eastern Europe: in Finland, Estonia, Hungary, Lithuania, Poland, Belarus, Ukraine, Romania and Russia (Kashinina et al, 2018;Lorenzini et al, 2014;Markov et al, 2016;Matosiuk et al, 2014;Olano-Marin et al, 2014;Plakhina et al, 2014;Plis et al, 2022). One of the reason could have been the interbreeding of the two species in the past, when their ranges overlapped to a large extent (Matosiuk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we investigated the mitochondrial DNA variability of Siberian roe deer throughout Asia as well as in the European regions, where the introgression between C. capreolus and C. pygargus had been recorded (Kashinina et Plis et al, 2022). We aimed to identify the general phylogenetic and phylogeographic patterns of the Siberian roe deer in its entire range of occurrence and, secondly, to elucidate the phylogeny of those Siberian haplotypes which were found within the European range of roe deer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not many studies have investigated the genetic diversity of European Roe Deer at a continental scale, and all have focused on maternally inherited mitochondrial DNA (mtDNA; Lorenzini et al 2014;Plis et al 2022aPlis et al , 2022b. To date, nuclear DNA (such as microsatellite DNA) of the species was studied only at the local or regional level (e.g.…”
mentioning
confidence: 99%